The role of women in the Korean church as a reflection of the Gospel of Matthew - Shin, In-Cheol (HTS teologiese studies, 2021)
This article aims to shed light on how the Korean church should set the role and status of women in the church, by dealing with the fact that women have contributed to the Korean church despite the gender discrimination and poor treatment they received from society. This article compares the role of women who influenced the revival of the early Korean church, and the story of the Canaanite woman in the Gospel of Matthew, in terms of dedication of faith. It also compares the stories of the roles of the Bible Women who greatly influenced the development of the early Korean church, and the stories of women who followed Jesus from Galilee to the crucifixion, in terms of loyalty of faith.Contribution: The purpose of this article is to bring acknowledgement and a fresh perspective on the role of Korean women in the modern church through the comparison of the dedication of faith and loyalty of faith of the women of the early Korean church and in the Gospel of Matthew.